(1398) philosophy, practice, and some problems of priority of regional cooperation-among developing countries الفلسفة والممارسة وبعض مشاكل أولوية التعاون الإقليمي بين البلدان النامية - moustafa, ahmed moustafa (The Institute Of National Planning., 2018)
The complicated, sensitive, and interrelated global economic. political, and social systems which underpin modern societies are hardly governable at present; and that they will maintain so unless and until, on the one hand, East-West confrontations are converted into actual cooperation .